2010
DOI: 10.1111/j.1365-2486.2009.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased atmospheric CO2 on the performance of an aquatic detritivore through changes in water temperature and litter quality

Abstract: Cold water woodland streams, where terrestrially derived organic matter fuels aquatic food webs, can be affected by increases in atmospheric CO 2 concentrations, as these are predicted to lead to increases in water temperature and decreases in organic matter quality. In fact, elevated CO 2 (580 ppm) decreased the initial phosphorus concentration of birch litter by 30% compared with litter grown under ambient conditions (380 ppm). Here, we first assessed the effect of differences in litter quality on mass loss,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 90 publications
3
55
0
1
Order By: Relevance
“…Accordingly, increased DIC-13 C content within the SSW at elevated temperatures suggests higher respiratory activities (Table 1). Elevated temperatures have been reported to increase respiration and food consumption in aquatic herbivores, detritivores and foraminifera (Bradshaw, 1961;Carr and Bruno, 2013), to lower grazing rates with simultaneously increased oxygen consumption (Ferreira et al, 2010) or to raise respiration to cover the costs of maintenance of protein metabolism levels (Whiteley and Faulkner, 2005). In general, DIC-13 C values in this experiment were very high compared to foraminiferal 13 C. It cannot be excluded that the foraminiferal cultures contained bacteria.…”
Section: Effect Of Temperature On Carbon and Nitrogen Uptakementioning
confidence: 99%
“…Accordingly, increased DIC-13 C content within the SSW at elevated temperatures suggests higher respiratory activities (Table 1). Elevated temperatures have been reported to increase respiration and food consumption in aquatic herbivores, detritivores and foraminifera (Bradshaw, 1961;Carr and Bruno, 2013), to lower grazing rates with simultaneously increased oxygen consumption (Ferreira et al, 2010) or to raise respiration to cover the costs of maintenance of protein metabolism levels (Whiteley and Faulkner, 2005). In general, DIC-13 C values in this experiment were very high compared to foraminiferal 13 C. It cannot be excluded that the foraminiferal cultures contained bacteria.…”
Section: Effect Of Temperature On Carbon and Nitrogen Uptakementioning
confidence: 99%
“…The concentration of structural carbohydrates (cellulose, hemicellulose, among others), which is higher in A. capillaris, could be another reason, as was reported by Picon-Cochard et al (2004), who found that grasses have a higher content of structural carbohydrates than forbs. In the same direction but for P, Ferreira et al (2010) and Ferreira and Chauvet (2011) observed that although alder leaves grown at elevated CO 2 had reduced P concentration, they decomposed faster than control leaves. Similarly, in terrestrial ecosystems, changes in plant composition induced by elevated CO 2 have been shown to have no effects on litter decomposition (Norby et al 2001).…”
Section: Discussionmentioning
confidence: 65%
“…Temperature has a major influence in biological and ecological processes: it may be a stressor by itself (Ferreira et al, 2010;McFeeters and Frost, 2011;Wojewodzic et al, 2011), it may modify the toxicity of chemicals (Prato et al, 2009;Lapointe et al, 2011;Vieira and Guilhermino, 2012), and may change abiotic conditions (e.g. water eutrophication and oxygen depletion) .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the ability of temperature to influence chemicals' toxicity (Boeckman and Bidwell, 2006;Prato et al, 2009), tests were performed at 10 and 20 xC. These are common temperatures in colder and warmer seasons, respectively, in the streams where the invertebrates were collected (Canhoto and Laranjeira, 2007;Ferreira et al, 2010). A. desmarestii, E. meridionalis and S. festiva were selected for this study because they play a key role in leaves decomposition in low-order streams where they occur, are abundant and easily maintained in the laboratory.…”
Section: Introductionmentioning
confidence: 99%